2007
DOI: 10.1007/s11096-007-9171-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in attitudes among Japanese patients after Pharmacist Law revision

Abstract: The rapid progression of drug information disclosure after enactment of the Pharmacist Law revision has likely resulted in drastic changes in patients' perception of their medications and led to improvements in medication adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The Bungyo ratio(number of legal prescriptions as a percentage of the total number of prescriptions) obtained the following findings. Although previous studies reported similar results,12,13 settings of these studies were large hospitals or single centers.Our study revealed the current status of patientsʼ satisfaction and understanding of drug information in the primary care setting.First, most patients were shown to be satisfied with the current provision of information regarding antihypertensive drugs. However, problems were seen in their understanding of the information provided.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The Bungyo ratio(number of legal prescriptions as a percentage of the total number of prescriptions) obtained the following findings. Although previous studies reported similar results,12,13 settings of these studies were large hospitals or single centers.Our study revealed the current status of patientsʼ satisfaction and understanding of drug information in the primary care setting.First, most patients were shown to be satisfied with the current provision of information regarding antihypertensive drugs. However, problems were seen in their understanding of the information provided.…”
mentioning
confidence: 70%
“…Iihara et al reported that, since the enactment of this revision, drug information disclosure to patients by pharmacists has rapidly become common practice and, as a result, patientʼs compliance with instructions for medication use has improved. 12 However, this study was conducted in a university hospital setting and most patients had rare or severe diseases, such as neurodegenerative diseases, inflammatory bowel disease, and malignancies. Therefore, it remains unclear whether this improvement trend is also present in community-based pharmacy setting.…”
Section: −10mentioning
confidence: 99%